Comparison of the mechanical response of B400c and B450c dual phase steel bar categories, in long terms - Charis Apostolopoulos; Argyro Drakakaki; Alkiviadis Apostolopoulos; Konstantinos Koulouris (Fracture and Structural Integrity)
In this work, the effects of chloride-induced corrosion on temp¬core B400c and B450c steel grades are evaluated, in terms of corrosion resis¬tance and mechanical characteristics, after the performance of Tensile and Low Cycle Fatigue Tests. Both steel categories, characterized by high strength and high ductility, have been used in existing structures, indicating that they demonstrate different performance against the ascribed corrosion environ¬ments. B450c steel grade seems to preserve higher energy reserves, ensuring higher expectancy to the corresponding reinforced concrete struc¬tures. Ad-ditionally, due to buckling and buckling reversal, both steel grades dem¬onstrate limited ductility at 4%. Finally, when cyclically stresses occur, crack nucleation is taking place, at the areas where sulphides, FeS and MnS can be found, leading to sub-surface crack propagation, interacting with external pits